Current pedagogical practices employed by Technical Vocational Education and Training college’s mathematics lecturers - Vimbelo, S.; Bayaga, A. (South African Journal of Higher Education, 2023)
Concerns are increasing about the pedagogies employed by technical vocational education and training (TVET) colleges, particularly regarding the teaching of mathematics, exacerbated by the perception that TVET colleges are inferior to other types of educational institutions. Regardless of TVET colleges’ need to produce skilled workers, the concerns increasingly impede accessibility and students’ preparedness with sufficient workplace skills. While there has been a call to address several of the aforementioned concerns, one that has thus far attracted limited attention despite its importance is the pedagogical practices TVET colleges employ, particularly in mathematics. Guided by social constructivism, the study upon which this article is based explored the pedagogical practices employed by current TVET college lecturers in the mathematics classroom and the limited number of students enrolled in mathematics-based disciplines in TVET. Through a purposive sampling technique, ten (10) mathematics lecturers from a single TVET college in Gauteng were selected to participate in the study. The thematic analysis of the data revealed that these lecturers relied heavily on traditional approaches to teaching ‒ the banking zone was the only approach used extensively ‒ and only allowed for students’ passive involvement with the use of resources limited to whiteboards and textbooks. The routine approach of reviewing homework followed by classwork was dominant and there was a lack of real-life examples. A key recommendation that emerged from the study was further training in various pedagogies and the use of resources in teaching, particularly in mathematics lessons and re-training in advanced pedagogical practices.